Change in running kinematics after cycling are related to alterations in running economy in triathletes - Bonacci, J.; Green, D.; Saunders, P. U.; Blanch, P.; Franettovich, M.; Chapman, A. R.; Vicenzino, B. (Journal of Science and Medicine in Sport, 2010)
Emerging evidence suggests that cycling may influence neuromuscular control during subsequent running but the relationship between altered neuromuscular control and run performance in triathletes is not well understood. The aim of this study was to determine if a 45 min high-intensity cycle influences lower limb movement and muscle recruitment during running and whether changes in limb movement or muscle recruitment are associated with changes in running economy (RE) after cycling. RE, muscle activity (surface electromyography) and limb movement (sagittal plane kinematics) were compared between a control run (no preceding cycle) and a run performed after a 45 min high-intensity cycle in 15 moderately trained triathletes. Muscle recruitment and kinematics during running after cycling were altered in 7 of 15 (46%) triathletes. Changes in kinematics at the knee and ankle were significantly associated with the change in VO2 after cycling (p < 0.05). The change in ankle angle at foot contact alone explained 67.1% of the variance in VO2. These findings suggest that cycling does influence limb movement and muscle recruitment in some triathletes and that changes in kinematics, especially at the ankle, are closely related to alterations in running economy after cycling.